Evaluation of Knowledge on Clinical Pharmacokinetics: A Crosssectional Study among Pharmacists in Hospital Raja Perempuan Zainab II, Kelantan - Siti Hamisah Said; Siti Latifah Azirah Mohd Noor; Nazmi Liana Azmi; Tan Kar Man; Suzana Mustafa (Asian Journal of Medicine & Health Sciences, 2023)
Clinical pharmacokinetics is the application of pharmacokinetics of drugs, especially drugs with small therapeutic window, to optimize the drug treatment in a patient. The aim of this study was to evaluate the knowledge of clinical pharmacokinetics among pharmacists in a tertiary hospital in Kelantan. A cross-sectional study was conducted using a self-developed research instrument. Following a thorough review of the literature, a multiple-choice questionnaire comprising of 28 questions on gentamicin/amikacin, vancomycin, valproic acid and phenytoin was created. It yielded a Cronbach alpha coefficient of 0.807 after being pilot tested on ten pharmacists. It was then distributed to all pharmacists working at Hospital Raja Perempuan Zainab II. Those who were on long leave or not available during the data collection period were excluded. All data were analysed using descriptive statistics, Chi-square test/Fisher’s exact test and independent t-test in Statistical Package for Social Sciences (SPSS) version 20. A total of 116 respondents was recruited into the study. The mean (SD) knowledge of clinical pharmacokinetics was 19.4 (4.8) with minimum score was 5.0 and maximum score was 28.0. It was observed that more pharmacists had poor knowledge (55.2%, n=64). In terms of responses to the questionnaire, four out of 28 questions had the most incorrect answers of >50%. They were question 7 (50.0%, n=58) regarding amikacin, question 17 (60.3%, n=70) pertaining to valproic acid as well as question 25 (51.7%, n=60) and question 28 (57.8%, n=67) which were about phenytoin. When further tested, it was noted that the knowledge of clinical pharmacokinetics was significantly associated with position (p=0.018), age (p=0.019) and working experience (p=0.016). The hospital pharmacists had a general poor knowledge in clinical pharmacokinetics especially the fully registered pharmacists who were older and had worked for a longer period of time. Therefore, an educational intervention is urgently needed to improve the knowledge in clinical pharmacokinetics among pharmacists working in Hospital Raja Perempuan Zainab II.